A Case Report Looking at An Incidental Finding of A Partial Anomalous Pulmonary Venous Connection (PAPVC) Using Magnetic Resonance Angiography (MRA) - Iqra Qamar; Mohammad Waleed (International Journal of Medical Students, 2018)
Background: Partial anomalous pulmonary venous connection (PAPVC) is a rare congenital defect where one or more of the pulmonary veins drain to the right atrium or its tributaries. This may cause a left to right shunt (LTRS) which may need surgical management. This case looks at a 58-year-old lady  with a background of Non-ST elevation myocardial infarction (NSTEMI) and co-morbidities, who presented with central chest pain. Cardiac magnetic resonance angiogram (MRA) was used in the  diagnosis and management of her PAPVC.